JAHON KОRPUS LINGVISTIKАSIDА DIАLЕKTАL KОRPUSLАR («CONTEMPORARY TECHNOLOGIES OF COMPUTATIONAL LINGUISTICS», 2024)
In this paper, using the examples of the Helsinki Corpus of British English Dialects (HD) and the Czech National Corpus of the Czech Dialects, the concept of dialect corpora relates to the progress of modern linguistics and the nature of the materials available to dialectologists in the school of vernacular studies. It is explained that it was developed taking into account the main directions.
Keywords: dialectology, dialect corpus, interview, informants, geographic location, SED, unicode.